Keanekaragaman Burung Lovebird (Agapornis fischeri) : Review - Nurmalasari, Nurmalasari; Rostakina, Weni; Aptini, Mipa (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Birds are wild animals that live in nature and have an important role in preserving the environment, for example as pest controllers, seed dispersers, and as pollinators. Lovebirds are animals from the aves group. This bird reproduces by oviparous or laying eggs. Eight of these bird species originate from the African continent, while the grey-headed lovebird species originates from the island of Madagascar. This bird is about 13-17 cm long, weighs 40-60 grams, and has a friendly nature. Lovebirds are the smallest birds from the parrot family. Lovebirds have compact bodies, short, blunt-tipped tails, and sharp beaks. Wild lovebirds are predominantly green with various colors on the upper body, depending on the species. There are many species of chirping birds/lovebirds. Each of them has their own unique sound and has their own strengths and weaknesses. There are some of them who sing (Agapornis fischeri) for a long time without stopping. There are also those who only make a slight, intermittent sound. Likewise, if you look at their physical appearance and color, each bird has its own unique color, most of them have beautiful and beautiful colors.